A new nuclear marker for quantitative analysis of wild boar and domestic pig meat in game meat products using PLAG1 zinc finger gene - Bukola M. Adenuga; Anita Spychaj; Magdalena Montowska (Scientific Reports)
Abstract Wild boar meat and pork are commonly added to game products, either as forefront or background ingredients. Due to their lower cost and wider availability compared to deer species, there is a potential for producers to misrepresent the inclusion of these species in more expensive game products. Therefore, a novel, highly specific TaqMan qPCR method targeting a single-copy 127-bp region of the PLAG1 zinc finger gene was developed for quantifying these subspecies in processed foodstuff. The individual qPCR systems, adapted to different processing conditions (raw and thermally treated), were implemented using a matrix-adapted reference system. These systems were validated using laboratory-prepared wild boar-in-beef patties. The assay achieved satisfactory performance parameters for fraud detection, reaching a sensitivity of 0.1 ng of wild boar or pig DNA, and both detection and quantification limits (LOD and LOQ) at 0.1% for raw and 0.5% (w/w) for thermally processed samples, respectively. Subsequently, commercial game meat and pork products were analyzed to assess their compliance with labeling claims. The results revealed instances of undeclared species, likely intentional mislabeling, and cross-contamination. The developed method can serve as a valuable tool for ensuring label compliance, preventing food fraud, and upholding halal specifications in the game meat industry.